Bigfoot - Cox, Greg, 1959- (New York, NY : Rosen Pub. Group, 2002)
Discusses the possible existence, sightings, and captures of the creature known as Bigfoot.
Includes bibliographical references (p. 45).
Keywords: Sasquatch -- Juvenile literature; Sasquatch